We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
46
8
avatar+409 

Hi guys,

 

just a question please. This sum:

 

\(x^{2 \over3}-20=44\)

\(x^{2 \over3}=64\)

\(x^{({1 \over3})^2}=64\)

Let K = \(x^{1 \over3}\)

So \(K^2=8^2\)

Therefore K = 8

 

Sub back:

\(x^{1 \over3}=8\)

\(x^{1 \over3}=2^3\)

\(x=2^{3*3} \)

\(x=512\)

 

Tis is my reasoning. I am led to believe this is wrong and HAS to be done this way:

 

\(K^2-64=0\)

\((K-8)(k+8)=0\)

\(K=8\) or \(K=-8\)

\((x^{1 \over3})^3=8^3\)     or      \((x^{1 \over3})^3=-8^3\)

x=512                          x= -512

 

Why must it be done this way?..why two answers?

 Apr 5, 2019
 #1
avatar+18049 
+3

x^(2/3) = 64     take sqrt of both sides

 

x^1/3 = + - 8     Cube both sides

x = 512   or -512  

 Apr 5, 2019
 #2
avatar+100166 
+3

The only thing I can see wrong with your logic is that you that if

x^2 =64

x can be poitive or negative 8

 

other than that, your way is fine.  :)

 

 

\(x^{2 \over3}-20=44\\ \left( x^{\frac{1}{3}}\right)^{2}=64\\ x^{\frac{1}{3}}=\pm8\\ x=8^3 \qquad or \qquad x=(-8)^3\\ x=512 \qquad or \qquad x=-512\\ \)

.
 Apr 5, 2019
 #3
avatar+99580 
+3

x^(2/3) - 20 = 44

 

x^(2/3) = 64

 

(x^2)^(1/3) = 64    cube both sides

 

x^2  = 64^3

 

x^2 = 262144    take both roots

 

x =  ±  √262144

 

x = ± 512

 

cool cool cool

 Apr 5, 2019
 #5
avatar+2067 
+2

Yeah All the top people who answer questions the most are answering Awsome.... smiley

Nickolas  Apr 5, 2019
 #4
avatar
+1

x^(2/3) ⇒ (-512)^(2/3) = 64 (-1)^(2/3) ≈ -32. + 55.4256 i    ?????

 Apr 5, 2019
 #6
avatar+100166 
+3

x^(2/3) ⇒ (-512)^(2/3) = 64 (-1)^(2/3) ≈ -32. + 55.4256 i    ?????

 

that is not correct

 

x^(2/3)

when x=-512

⇒ (-512)^(2/3)

= (64) *(-1)^(2/3)   true

 

       (-1)^(2/3) = [(-1)^2]^(1/3) = [1]^(1/3) = 1

       or

      (-1)^(2/3) = [   (-1)^(1/3)   ]^(2) = [-1]^(2) = 1

      either way

 

= (64) *(-1)^(2/3) 

=  +64

 

 

I am glas you showed us your confusion.  People do not learn if they do not ask questions  :)

Melody  Apr 5, 2019
 #7
avatar+409 
+3

yep yep....I have it...a square root ALWAYS has a positive and negative answer...my my...how could I forget that????.....Thank you to all who replied..I do appreciate..

juriemagic  Apr 5, 2019
 #8
avatar+100166 
+2

We know you appreciate us Juriemagic that is why we are always quick to answer your questions.

(At least we try to be and I think we usually are)

 

I always appreciate your good manners too  laugh

Melody  Apr 5, 2019

7 Online Users